Proceedings of the LST International Cohference on Geography and Education (ICGE 2016) 2017
DOI: 10.2991/icge-16.2017.46
|View full text |Cite
|
Sign up to set email alerts
|

Study of Population Growth and Land Use Change Impact of Intrusion on Pekalongan City

Abstract: Abstract-The2 , and second 27,18km 2 . The impact of land use change and population growth is an intrusion. Based on laboratory tests show that Pekalongan city intrusion on high category. The region within distance 500-600m from the coastline has salinity level of 6,7 to 15.5%, 800-900m has a salinity level of 2,9 to 6.6%, 1-1.5km has a salinity level of 1,4 to 2,8. Conclusion, land use change on Pekalongan City rather high, especially shrub, and dry agriculture changes into a settlement and built area. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The phenomenon of tidal flooding in Pekalongan has made environmental conditions worse, Saline water is the most common problem of water quality in the coastal city, especially in developing countries such as Indonesia. [17]. In fulfilling water needs the community uses underground water sources known as Pamsimas and PDAM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenomenon of tidal flooding in Pekalongan has made environmental conditions worse, Saline water is the most common problem of water quality in the coastal city, especially in developing countries such as Indonesia. [17]. In fulfilling water needs the community uses underground water sources known as Pamsimas and PDAM.…”
Section: Resultsmentioning
confidence: 99%
“…Water conditions in PDAM that are not smooth cause seawater to enter the pipes, causing the water to be unsuitable for consumption and the people of North Pekalongan prefer to use underground water sources again. The use of underground water sources is actually not good for the environment itself, Based on laboratory tests show that Pekalongan city intrusion on high category [17]. The region within distance 500-600m from the coastline has salinity level of 6,7 to 15.5%, 800-900m has a salinity level of 2,9 to 6.6%, 1-1.5km has a salinity level of 1,4 to 2,8.…”
Section: Resultsmentioning
confidence: 99%
“…High salinity affected in 914.33 hectares [13]. The zone within a distance of 500-600m from the shoreline has 6.7 to 15.5% salinity, 800-900m has 2.9 to 6.6% salinity, and 1-1.5km has 1.4 to 2.8% salinity [14]. The study used a DRASTIC method showed that the Pekalongan City groundwater experienced vulnerability at moderate to high levels.…”
Section: Groundwater Characteristicsmentioning
confidence: 99%
“…Flash-oods and tidal-ood threaten approximately 40% of the lowland areas in Semarang City by sea level rises. In another part, more problems worsen ood disaster caused by high population around riverbank areas (Suharini et al, 2017). During 2018, at least 18% of the total disasters in Semarang City are ood disasters, include ash oods and inundation (BPBD, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Besides that problems, high exploration of gases and groundwater extraction make land subsidence that surges ood risk (Chaussard et al, 2013) . Increased population, high business activity, and resources may lead people migration and occupation that increase environmental damage and disasters (Hapsari & Zenurianto, 2016;Mark, 2017;Suharini et al, 2017) Community-based resilience has developed in Semarang City to help them confronting ash oods and inundation problems. It has leverage community participation in early warning of ood disaster (Sari & Prayoga, 2018), even though it still needs more improvement, especially in community understanding and awareness of their needs.…”
Section: Introductionmentioning
confidence: 99%